1979
DOI: 10.1111/j.1467-2494.1979.tb00216.x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical effects of unsaponifiable lipidic components of avocado and soya bean administered percutaneously on the connective tissue components of hairless rat skin

Abstract: Synopsis The unsaponifiable lipidic fractions of avocado and soya bean were administered percutaneously, on the dorsal skin of hairless rats for 15 days, in a 5% sweet almond oil solution. This treatment produced a modification of dermal connective tissue components. The biochemical analysis showed an increase of soluble proteins, especially of salt soluble collagen together with a decrease of proteins insoluble in neutral buffer. The ratio, soluble proteins:insoluble proteins, increases as well as the ratio s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…8 ASU both applied percutaneously and orally also produced an increase of soluble collagen and a decrease of insoluble collagen in animal models by activating connective tissue metabolism. 9,10 The ASU action on the skin collagen metabolism may explain the beneficial effect on scleroderma reported by several authors. 8,11 Both vitamin E 12,13 and PABA 14 supplementation resulted in improvements in the skin of scleroderma patients due to an anti-fibrotic action.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…8 ASU both applied percutaneously and orally also produced an increase of soluble collagen and a decrease of insoluble collagen in animal models by activating connective tissue metabolism. 9,10 The ASU action on the skin collagen metabolism may explain the beneficial effect on scleroderma reported by several authors. 8,11 Both vitamin E 12,13 and PABA 14 supplementation resulted in improvements in the skin of scleroderma patients due to an anti-fibrotic action.…”
Section: Discussionmentioning
confidence: 93%
“…In the literature, avocado/soybean unsaponifiable (ASU), which is an extract prepared from avocado and soybean oil, has been shown to exert an anti‐inflammatory effect . ASU both applied percutaneously and orally also produced an increase of soluble collagen and a decrease of insoluble collagen in animal models by activating connective tissue metabolism …”
Section: Discussionmentioning
confidence: 99%
“…For example, a mixture of avocado and soya bean nonsaponifiable lipids (PIAS 300) is widely prescribed to stimulate the metabolism of skin dermis fibroblast and cell proliferation at a wound site. In vivo, PIAS modifies constituents of connective tissue and increases the ratio of soluble collagen to insoluble collagen [9,10]. In vitro, its effect on the proliferation of fibroblasts is only detectable when cultures are performed in abnormal conditions such as low incubation temperature or reduced concentration of serum in culture medium [ 111.…”
Section: Introductionmentioning
confidence: 99%
“…Biochemical studies performed on rats after oral or topical administration have shown that non-saponifiables increase metabolism of skin dermis. PIAS decrease the level of cross-linked collagen and increase acido-soluble collagen (6,7,8,9). Simultaneously, the elasticity of whole skin increases and the thermal stability of collagen decreases (10).…”
Section: Introductionmentioning
confidence: 99%